2021
DOI: 10.3390/electronics10202530
|View full text |Cite
|
Sign up to set email alerts
|

Analog Gaussian Function Circuit: Architectures, Operating Principles and Applications

Abstract: This review paper explores existing architectures, operating principles, performance metrics and applications of analog Gaussian function circuits. Architectures based on the translinear principle, the bulk-controlled approach, the floating gate approach, the use of multiple differential pairs, compositions of different fundamental blocks and others are considered. Applications involving analog implementations of Machine Learning algorithms, neuromorphic circuits, smart sensor systems and fuzzy/neuro-fuzzy sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 93 publications
(284 reference statements)
0
2
0
Order By: Relevance
“…The volume of input dimensions is contingent on the multidimensional Gaussian function circuit. While there exist various circuits that yield PDFs, extant literature confines their application to dimensions of a modest scale, typically less than 16 [20,65].…”
Section: Proposed Design Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The volume of input dimensions is contingent on the multidimensional Gaussian function circuit. While there exist various circuits that yield PDFs, extant literature confines their application to dimensions of a modest scale, typically less than 16 [20,65].…”
Section: Proposed Design Methodologymentioning
confidence: 99%
“…A broad spectrum of bump circuits has been developed for numerous applications [20]. However, for the purposes of this research, a modified version of the bump circuit (aspect ratio equal to 7) [65], as shown in Figure 3, has been employed to enhance the quality and resilience of the resulting Gaussian curve.…”
Section: Gaussian Function Circuitmentioning
confidence: 99%
See 1 more Smart Citation
“…Architectures tailored specifically to ML algorithms and models in an analog hardware implementation leverage circuits grounded in Gaussian functions [38]. A subsection consolidates the distinctive features of system-level implementations integrated with Gaussian function circuitry.…”
Section: Background 21 Related Literaturementioning
confidence: 99%
“…Pursuing a probabilistic inference, significant strides have been made in recent years to develop devices capable of physically emulating the characteristics of a Gaussian function 30 33 . This physics-based computing approach, using the Gaussian devices, holds the potential for a revolutionary enhancement in energy efficiency, thereby enabling efficient operation of GMMs with highly constrained resources.…”
Section: Introductionmentioning
confidence: 99%